2023
DOI: 10.1007/s10531-023-02694-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity in residential gardens: a review of the evidence base

Richard J. Delahay,
D. Sherman,
B. Soyalan
et al.

Abstract: Residential gardens are a principal component of urban green infrastructure throughout the world and their potential positive contributions to biodiversity are increasingly recognised. But the characteristics of gardens reflect the needs, values and interests of individual households. The present review summarises evidence from studies of garden biodiversity published in the scientific literature, describes major themes and identifies important knowledge gaps. A search of the Web of Science database identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 178 publications
0
1
0
Order By: Relevance
“…Some efforts have been made to understand the relationships between garden size and biodiversity in the urban setting (Majewska & Altizer, 2018). A recent extensive review of the literature showed that several studies especially link garden size to positive effects for plants biodiversity (Delahay et al, 2023). Garden size being important to insect diversity has also been confirmed by a meta-anlysis, yet importantly only includes studies on larger gardens (Majewska and Altizer, 2020; 6.1m 2 – 70 000m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been made to understand the relationships between garden size and biodiversity in the urban setting (Majewska & Altizer, 2018). A recent extensive review of the literature showed that several studies especially link garden size to positive effects for plants biodiversity (Delahay et al, 2023). Garden size being important to insect diversity has also been confirmed by a meta-anlysis, yet importantly only includes studies on larger gardens (Majewska and Altizer, 2020; 6.1m 2 – 70 000m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first studies aiming to detect the biodiversity of gardens in Western Europe and North America were conducted at the beginning of the 1990s (Delahay et al, 2023). Interest in the role of urban and suburban gardens in the preservation and support of urban ecosystems has increasingly gained interest since then (Delahay et al, 2023) and showed that even small, but resource-rich, garden habitats can significantly increase insect diversity (Griffiths-Lee et al, 2022) and support ecological services such as pollination, biological pest control or climate regulation (Andersson et al, 2007; Cavan et al, 2021). Gardens can function as ecological corridors or stepping stones for a multitude of organisms in the otherwise barren and often hostile urban landscape and, particularly when they have favourable habitat features (e.g.…”
Section: Introductionmentioning
confidence: 99%